Identifikasi Tingkatan Warna Pada Kopi Roasting Menggunakan Metode HSV Berbasis Mobile - Ryansyah, Ryansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Image processing (digital image processing) is a discipline that learns about image processing techniques. The image referred to in this study is a static image derived from sensor vision (webcame). Mathematically, an image is a continuous function with light intensity in a two-dimensional field. In order to be processed with digital computers, an image must be presented numerically with discrete values. A digital image can be represented by a two dimensional matrix f (x, y) consisting of M columns and N rows. In this study the color method used is the HSV color method, that is, the image (RGB) is converted into HSV to compare the original image with the results of RGB to HSV conversion. Image color processing, there are various models, one of them is the model of hue, saturation, value (HSV). By using this model, an object with a certain color can be detected and reduce the influence of the intensity of light from the outside. Coffee roasting is one of the processes of making coffee that is ready to be drunk and this roasting coffee uses a level of maturity that is very different according to the taste of the audience but until now no roaster has been able to correctly guess the roasting coffee level that has been made so from that the author took the title